Optimum Use of Sugar Cane Straw Ash in Alkali-Activated Binders Based on Blast Furnace Slag - Bassan de Moraes, Joao Claudio [UNESP]; Tashima, Mauro Mitsuuchi [UNESP]; Pinheiro Melges, Jose Luiz [UNESP]; Akasaki, Jorge Luis [UNESP]; Monzo, Jose; Victoria Borrachero, Maria; Soriano, Lourdes; Paya, Jordi (Asce-amer Soc Civil Engineers, 2018)
Alkali-activated binders (AABs) are a material obtained from the combination of a solid precursor and an alkaline activating solution. In this study, one solid precursor used was blast-furnace slag (BFS) and the other was an agro waste: sugar cane straw ash (SCSA). Sodium hydroxide was used for preparing activating solutions. In order to reach the potential reactivity of the SCSA, a study varying the BFS/SCSA mass ratio and H2O/Na2O molar ratio was carried out. The BFS/SCSA ratio varied from 100/0 to 70/30, and H2O/Na2O was studied in the range of 11.1-18.5. To fulfill this objective, specimens were assessed by their compressive strength of mortars and microstructural studies of pastes [X-ray diffraction (XRD); thermogravimetric analysis (TGA); Fourier transform infrared spectroscopy (FTIR); and field emission scanning electron microscopy (FESEM)] in the curing time range of 3-90 days at 25 degrees C. Results from these tests showed that the best BFS/SCSA and H2O/Na2O ratios were 70/30 and 18.5, respectively. This study revealed an interesting valorization of the SCSA as a complementary precursor in BFS-based AABs because of the improvement of mechanical properties and the reduction in the consumption of BFS in AAB.
Keywords: Agro waste; Optimum replacement; Microstructural studies; Compressive strength